'Battle against Their Own Minds' Notes on Literate Kerala - Krishna Kumar (Economic and Political Weekly February 12, 1994, 1994)
The idea that illiterates are living in a dark age because of their illiteracy underlies the national literacy programme, yielding the stereotypes of the illiterate as submerged in a sea of darkness and the literate as bathing in the light of every kind of awareness. The human goals of education are sacrificed fully when the existing stratification of society is reified thus by a baseless, indeed irrational, use of knowledge to classify people